Concomitant immunity leads to retardation or acceleration of the growth of Rous sarcomas in genetically resistant or susceptible inbred lines of chickens - Plachý, J; Karakoz, I; Benda, V (Folia biologica, 1986)
We report results on the age-dependent effect of the B (MHC) genotype on resistance to the growth of a second RSV tumour in chickens from highly inbred lines genetically resistant or susceptible to progressive growth of primary RSV-induced tumours. Furthermore, the second inoculation of RSV caused either accelerated or retarded growth of the primary tumours induced by the same virus. These two types of response to a second challenge with RSV were controlled by alleles of the chicken major histocompatibility (B) complex. The retarded growth of the primary tumours was found to be thymus-dependent. Furthermore, a clear-cut trans-complementation effect of two B alleles on the response to RSV challenge was demonstrated.
Keywords: testy genetické komplementace; ptačí sarkom; Thymus Gland; genotyp; Animals; Age Factors; thymus; Thymectomy; Chickens; věkové faktory; alely; Sarcoma, Avian; zvířata; kur domácí; Major Histocompatibility Complex; hlavní histokompatibilní komplex; Genetic Complementation Test; Genotype; thymektomie; Alleles